1976
DOI: 10.1007/bf00218715
|View full text |Cite
|
Sign up to set email alerts
|

Insect UV-, and green-photoreceptor membranes studied by the freeze-fracture technique

Abstract: The membranes of the microvilli of UV- and green-photoreceptors of the ant Myrmecia gulosa have been studied with the freeze-fracture technique. Both inner fracture faces, the cytoplasmic P-face and the extracellular E-face, are covered by globular particles. The P-face particles appear to be randomly distributed, occasionally forming clusters. Their density is about 7,000/mum2, and their mean diameter is 8.5 nm. The E-face particles, however, are arranged in an ordered square pattern with a center-to-center s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In all cases in which both the rhabdomeric particle density and rhodopsin content were studied, the mutations or vitamin A deprivation was found to reduce both these quantities, supporting the idea that at least the majority of the rhabdomeric membrane particles are closely associated with rhodopsin. Vitamin A deprivation and the mutations also reduced the number of particles in the plasma membrane as in the rhabdomeric membrane, suggesting that both classes of membrane contain rhodopsin .Freeze-fracture studies of the photoreceptors have shown that there are numerous membrane particles on the fracture face of both the outer segment disk membrane of vertebrate photoreceptors (36, 37, and references cited therein) and the rhabdomeric microvillar membrane of invertebrate photoreceptors (3,5,8,9,14,22,26,32) . Several lines of evidence suggest that these membrane particles are correlated with the presence of rhodopsin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases in which both the rhabdomeric particle density and rhodopsin content were studied, the mutations or vitamin A deprivation was found to reduce both these quantities, supporting the idea that at least the majority of the rhabdomeric membrane particles are closely associated with rhodopsin. Vitamin A deprivation and the mutations also reduced the number of particles in the plasma membrane as in the rhabdomeric membrane, suggesting that both classes of membrane contain rhodopsin .Freeze-fracture studies of the photoreceptors have shown that there are numerous membrane particles on the fracture face of both the outer segment disk membrane of vertebrate photoreceptors (36, 37, and references cited therein) and the rhabdomeric microvillar membrane of invertebrate photoreceptors (3,5,8,9,14,22,26,32) . Several lines of evidence suggest that these membrane particles are correlated with the presence of rhodopsin.…”
mentioning
confidence: 99%
“…Freeze-fracture studies of the photoreceptors have shown that there are numerous membrane particles on the fracture face of both the outer segment disk membrane of vertebrate photoreceptors (36,37, and references cited therein) and the rhabdomeric microvillar membrane of invertebrate photoreceptors (3,5,8,9,14,22,26,32) . Several lines of evidence suggest that these membrane particles are correlated with the presence of rhodopsin.…”
mentioning
confidence: 99%
“…These two opsins are only 38% identical to the opsins previously cloned from these two species (Popp et al, 1996), and are most similar (88%) to the ultraviolet-sensitive opsin from honeybees (Townson et al, 1998). Ants are known to have two visual pigments, a long wavelength-sensitive photoreceptor with a )~max near 510 nm and shorter ultraviolet sensitive photoreceptor with ~'max near 350 nm (Menzel 1975;Nickel and Menzel 1976). The opsin cDNAs previously obtained from these same cDNA libraries code for the long-wavelength visual pigments (Poppet al, 1996).…”
Section: Resultsmentioning
confidence: 97%
“…Some experimental data from the bulldog ant (NICKEL and MENZEL, 1976), where particles were found in both layers under certain experimental conditions, indicate a similar transformation in membrane pattern. The clusters of particles in the inner layer showed a more irregular hexagonal arrangement, whereas the particles of the outer layer (E-face, the same as the B-face) were arranged in rows, aligned with the axis of the microvillus.…”
Section: Structure and Function Of The Microvillusmentioning
confidence: 81%
“…(a) Three dimensional scheme of the microvillus structure. Particles of comparable size were found in the rhabdomeres of the honeybee (PERRELET et a1., 1972) and of the bulldog ant Myrmecia gulosa (NICKEL and MENZEL, 1976). (b) View from within the microvillus membrane.…”
Section: Structure and Function Of The Microvillusmentioning
confidence: 99%